Unidades de traducción culturalmente marcadas: propuesta de clasificación dinámica con fines traductológicos - Mendoza García, Inma (HERMES - Journal of Language and Communication in Business, 2018)
In the context of Translation Studies, this paper presents a proposal for classifying culturally marked translation units from a functional dynamic perspective that is considered to be more useful for both translation practice and translation-related research than other taxonomies so far suggested by the majority of theorists. For this purpose, first I provide an overview of the current state of the art in research on these specific translation units with regard to their designation, concept and classification. Second, I conduct a critical analysis of the heterogeneity of designations and definitions as well as of the static taxonomies so far prevailing in scientific literature in this respect. Third, I select a designation for these sorts of units and justify the decision made. Fourth, I provide a detailed description of the concept and its nature. Finally, I design a classificatory model that is not based on a mere classification of culture-related areas and topics but takes into account all the intratextual and extratextual factors involved in the translation process. The proposal put forward is guided by two main parameters: the degree of lingüistic and cultural (in)equivalence between the source system and the target system and the level of knowledge the reader is supposed to possess about the culturally marked textual units.